The frequency and clinical significance of centromere enumeration probe 17 alterations in human epidermal growth factor receptor 2 immunohistochemistry‐equivocal invasive breast cancer. Issue 4 (8th August 2022) - Katayama, Ayaka; Starczynski, Jane; Toss, Michael S; Shaaban, Abeer M; Provenzano, Elena; Quinn, Cecily M; Callagy, Grace; Purdie, Colin A; Millican‐Slater, Rebecca; Purnell, David; Chagla, Leena; Oyama, Tetsunari; et al.
Abstract : Background and aims: Chromosome 17 alterations affect the assessment of HER2 gene amplification in breast cancer (BC), but its clinical significance remains unclear. This study aimed to identify the prevalence of centromere enumeration probe 17 (CEP17) alterations, and its correlation with response to neoadjuvant therapy (NAT) in BC patients with human epidermal growth factor receptor 2 (HER2) immunohistochemistry‐equivocal score. Methods and results: A large BC cohort ( n = 6049) with HER2 immunohistochemistry score 2+ and florescent in‐situ hybridisation (FISH) results was included to assess the prevalence of CEP17 alterations. Another cohort ( n = 885) with available clinicopathological data was used to evaluate the effect of CEP17 in the setting of NAT. HER2‐ amplified tumours with monosomy 17 (CEP17 copy number < 1.5 per nucleus), normal 17 (CEP17 1.5–< 3.0) and polysomy 17 (CEP17 ≥ 3.0) were observed in 16, 59 and 25%, respectively, compared with 3, 74 and 23%, respectively, in HER2 ‐non‐amplified tumours. There was no significant relationship between CEP17 alterations and pathological complete response (pCR) rate in both HER2 ‐amplified and HER2 ‐non‐amplified tumours. The independent predictors of pCR were oestrogen (ER) negativity in HER2‐ amplified tumours [ER negative versus positive; odds ratio (OR) = 11.80; 95% confidence interval (CI) = 1.37–102.00; P = 0.02], and histological grade 3 in HER2 non‐amplified tumours (3 versus 1, 2; OR = 5.54; 95% CI = 1.61–19.00; P = 0.007). Conclusion: The impacts of CEP17 alterations are not as strong as those of HER2 /CEP17 ratio and HER2 copy number. The hormonal receptors status and tumour histological grade are more useful to identify BC patients with a HER2 immunohistochemistry‐equivocal score who would benefit from NAT. Abstract :